The possibilities of interventional radiology before and after orthotopic liver transplantation - A. V. Moiseenko; A. A. Polikarpov; D. A. Granov; P. G. Tarazov; C. V. Shapoval; A. R. Sheraliev; A. G. Karahanova (Вестник трансплантологии и искусственных органов, 2018)
Presented the case of a combined approach preparation of 47 years old patient with primary biliary cirrhosis for orthotopic liver transplantation (OLT) and arterial flow  insufficiency correction after surgery. The patient was under waiting list for OLT due  liver cirrhosis progression. The patient underwent Intraportal infusion of autologous bone marrow mononuclear cells (MNC) which is allowed temporary  stabilized the cirrhotic transformation. The transjugular intrahepatic portosystemic  shunt (TIPS) procedure performed due to portal hypertension progression with  episodes of bleeding from the esophageal and gastric varices, that allowed to  receive organ donor and OLT. At 6 months after OLT the patient had clinical signs of  a jaundice caused by splenic artery steal syndrome which was corrected by endovascular intervention: splenic artery trunk embolization.